2020
DOI: 10.3390/jcm9061934
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Imaging in the Management of Choroidal Neovascularization Secondary to Central Serous Chorioretinopathy

Abstract: The diagnosis and treatment of choroidal neovascularization (CNV) in eyes with chronic central serous chorioretinopathy (CSCR) can be challenging. The purpose of this study was to classify eyes with suspected CNV using multimodal imaging. The effect of intravitreal anti-vascular endothelial growth factor (VEGF) was assessed and compared to controls. This retrospective study included chronic CSCR patients with suspected secondary CNV who received intravitreal bevacizumab. Eyes were divided into “definite CNV” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A panel of experts recently recommended a new definition of macular neovascularisation (MNV) to replace the old term of choroidal neovascularisation 5. In recent research, CSC has been considered a part of the pachychoroid spectrum disease and may be complicated by the secondary formation of exudative MNV6 7; however, the mechanism of secondary MNV has not yet been determined. Some studies have found an increased prevalence of MNV after treatment with laser8 9 or photodynamic therapy (PDT)9 10 in CSC, which may be caused by rupture of the BM after laser therapy or choroidal ischaemia and excessive vascular endothelial growth factor (VEGF) production after PDT 9…”
Section: Introductionmentioning
confidence: 99%
“…A panel of experts recently recommended a new definition of macular neovascularisation (MNV) to replace the old term of choroidal neovascularisation 5. In recent research, CSC has been considered a part of the pachychoroid spectrum disease and may be complicated by the secondary formation of exudative MNV6 7; however, the mechanism of secondary MNV has not yet been determined. Some studies have found an increased prevalence of MNV after treatment with laser8 9 or photodynamic therapy (PDT)9 10 in CSC, which may be caused by rupture of the BM after laser therapy or choroidal ischaemia and excessive vascular endothelial growth factor (VEGF) production after PDT 9…”
Section: Introductionmentioning
confidence: 99%
“…Because optical coherence tomography (SD-OCT) is a non-invasive examination, it is particularly useful in cases of suspected MNV. An indication for a type 1 MNV can be shallow irregular retinal epithelium elevation (SIRE), for a type 2 MNV the subretinal hyperreflective material (SHRM) and for a type 3 MNV intraretinal edema with intraretinal hyperreflective material [4]. It is also suitable as a non-invasive monitoring of the disease course by assessing intraretinal and/or subretinal fluid, fibrosis, atrophy, and pigment epithelial detachments [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not completely understood whether those type 1 CNVs are really responsible for the exudation, or whether they might be considered a compensatory effect to a subtle and chronic hypossia secondary to a sick choroid. Recently, researchers showed that in patients with cCSC, CNV demonstrated by OCT angiography responded well to bevacizumab injections [ 79 ].…”
Section: The Role Of Anti-vascular Endothelial Growth Factor (Antimentioning
confidence: 99%